Effect of Ayurvedic polyherbal compound (syrup Kasahara Dashemani) in the management of Vataja Kasa (acute cough) in Children - An open-label single-arm clinical study - Neha Yadav; Vijay Kumar Pathak; Arun Kumar Mahapatra; Rajagopala Shrikrishna (Wolters Kluwer Medknow Publications, 2023)
Background: Cough is one of the most common clinical presentations encountered frequently in the pediatric population and is correlated with Kasa Roga in Ayurveda. Kasa Roga (cough) is distressing to children and hampers their quality of life. Vataja Kasa (acute cough) if left untreated becomes chronic and distressing to both the child and the parents. Various ayurvedic formulations with cough-suppressing effects have been documented in classical texts that are cost-effective; Kasahara Dashemani is one such ayurvedic polyherbal compound mentioned by Acharya Charaka, possessing antitussive properties that are also evidenced by previous studies. Objectives: The objective of this study was to assess the efficacy of Syrup Kasahara Dashemani on classical cardinal features of Vataja Kasa (acute cough), cough scores, and hematological parameters. Materials and Methods: The present study was an interventional prospective, open-label, single-arm clinical trial in which 30 children between the age group of 5 and 15 years presenting with classical cardinal features of Vataja Kasa (acute cough) were administered with syrup Kasahara Dashemani orally in various age-dependent doses calculated by using Young's formula, every 6 h for 1-month duration. Assessment criteria included six classical cardinal features of Vataja Kasa, daytime and nighttime cough scores, and hematological investigations. Results: On assessing the outcome parameters, significant improvement was observed in all the six classical cardinal features of Vataja Kasa (acute cough), daytime and nighttime cough scores (P < 0.0001), eosinophil count (P < 0.05), absolute eosinophil count (P < 0.05), and erythrocyte sedimentation rate (P < 0.05) in all the study subjects. Conclusion: Syrup Kasahara Dashemani can help alleviate Vataja Kasa (acute cough) in the pediatric population.